Mnenje prebivalcev Slovenije o pomenu gozdov in gozdarstva - Simončič, Tina (Acta silvae et ligni, 2018)
The research aims at assessing the Slovenian public opinion on the importance of forests and forest management. 1014 surveys were completed by randomly selected adult citizens of the RS proportionally in regard to the country%s statistical regions. The survey included 10 sections and 74 Likert-type statements. Slovenian public believes that the most important functions of forests are environmental functions, followed by wood production and protection against natural hazards, social functions, whereas the least important are gathering non-wood forest products and hunting. More than 90 % of respondents think that forests are important for multiple functions. 74 % of the public supports free access, 60 % of them supports the right to gather non-wood forest products. The majority of them believe that the state should invest funds for supporting environmental functions. The statements on free access and importance of forests for recreation are the strongest factors in discriminating the groups of forest owners and non-owners.
Keywords: forest functions; forest management; forest non-owners; forest owners; forest policy; forest values; funkcije gozdov; gospodarjenje z gozdovi; gozdarska politika; javna anketa; lastniki gozdov; nelastniki gozdov; public opinion poll; vrednost gozdov